Strategi Komunikasi Pemasaran Bisnis Jasa Pengiriman Barang (Analisis Kampanye Roadshow Mandiri Sejahtera Sdn-Bhd Malaysia) - Fahmi, Tubagus (MediaKom : Jurnal Ilmiah Komunikasi, 2015)
The high number of Indonesian Migrant Workers (TKI) in Malaysia contribute to the high consumption of the workers in the shipment of goods from Malaysia to Indonesia. This is a huge market opportunity impact to competition between freight services company in Malaysia. The various reality of bitterness issues, pride and the strength existence of community network among the majority of migrant workers as well as the emotional connection between them indirectly into its own power to contribute of the market opportunities. This study was conducted to know the marketing communication strategy undertaken by Mandiri Sejahtera Sdn-Bhd (MS Cargo) for the netwotk node or figures in the network workers who become sales agent services in order to encourage a target of marketing. Through qualitative research methods with case study approach, the author analyzed Marketing Communication Mix used by MS Cargo through the Marketing Public Relations activities in the form of Roadshow Campaign in 2012 for its targets in various states of Malaysia. The results of this study indicate that the Roadshow Campaign in addition an impact on increasing sales of the company’s services through the agency of the workers, This study also found a symbiotic mutualism obtained between the company, the agents (TKI) and the government of Indonesia. Mutual needs in a spirit of effort and a sense of nationhood that realized in the form of loyalty, work culture; work ethic and the spirit of TKI’s independence. Keywords: Strategy, Marketing Communication Mix, Roadshow Campaign, Marketing PR.